Isogenous Asymmetric–Symmetric Acceptors Enable Efficient Ternary Organic Solar Cells with Thin and 300 nm Thick Active Layers Simultaneously - Bai, Hai‐Rui; An, Qiaoshi; Jiang, Mengyun; Ryu, Hwa Sook; Yang, Jie; Zhou, Xue‐Jiao; Zhi, Hong‐Fu; Yang, Can; Li, Xiong; Woo, Han Young; Wang, Jin‐Liang (Advanced functional materials, 2022)
Integrating desirable light absorption, energy levels, and morphology in one matrix is always the aspiration to construct high‐performance organic solar cells (OSCs). Herein, an asymmetric acceptor Y6‐1O is incorporated into the binary blends of acceptor Y7‐BO and donor PM6 to prepare ternary OSCs. Two isogenous asymmetric–symmetric acceptors with similar chemical skeletons tend to form alloy‐like state in blends due to their good compatibility, which contributes to optimizing the morphology for efficient charge generation and extraction. The complementary absorption of two acceptors helps to improve the photon harvesting of ternary blends, and the higher lowest unoccupied molecular orbital (LUMO) energy level of Y6‐1O offers the chance to uplift the mixed LUMO energy levels of acceptors. Combining the aforesaid benefits, the ternary OSCs with 10 wt% Y6‐1O produce a top‐ranked power conversion efficiency (PCE) of 18.11% with simultaneously elevated short‐circuit current density, open‐circuit voltage, and fill factor in comparison to Y7‐BO‐based binary devices. Furthermore, the optimized ternary OSCs with ≈300 nm active layers obtain a champion PCE of 16.61%, which is the highest value for thick‐film devices reported so far. This work puts forward an avenue for further boosting the performance of OSCs with two isogenous acceptors but different asymmetric structures. The synergistically optimized light absorption, energy levels, and morphology, by incorporating an asymmetric isogenous acceptor Y6‐1O in PM6:Y7‐BO‐based ternary organic solar cells (OSCs), is demonstrated. The optimized ternary OSCs produce a top‐ranked power conversion efficiency (PCE) of 18.11% and with ≈300 nm active layers obtain a champion PCE of 16.61%, which is the highest value for thick‐film devices reported so far.